Performance appraisal: A study on staff attitude and performance / Raja Zirwatul Aida Raja Ibrahim, Azlina Abu Bakar @ Mohd and Madihah Mohamad Shukri - Raja Ibrahim, Raja Zirwatul Aida; Abu Bakar @ Mohd, Azlina; Mohamad Shukri, Madihah (2004)
Performance appraisal that is design appropriately for the staff and organization is very important. In actual practice, performance appraisal system often did not meet the objectives and produce unsatisfactorily result. A major mistake made by companies is failure to identify what constitute effective performance appraisal. Since the main objective of the study is to come out with what is the ideal practising performance appraisal in the organization, this study examined the attitude of appraiser and appraisec towards performance appraisal system. Results revealed that there are significant different on their attitudes related to giving staff an opportunity to express and communicate ideas, state how job could be improved, enable the company to convey its values and goals and help the company identify training and development need. For remaining issues such as the importance of performance appraisal, appraisec understanding on performance appraisal and satisfaction with performance appraisal were discussed in descriptive statistics indicate the perception of appraisec towards current appraisal system. Furthermore, the participants show the positive perception towards performance appraisal in term of improvement in staff performance and providing two ways communication or feedback. Nevertheless, negative perception is presented in dealing with the current performance appraisal suitability and uncertainty either the appraisal system achieves the objectives or not. The findings have numerous implications towards the organisation and staff in achieving more effective and ideal performance appraisal system. This is important to enable the organization to review on appraisers training on how to effectively conduct appraisal, room for communication or feedback and the bias challenge which are regarded as the pitfalls in practicing performance appraisal. Some interventions are previewed to overcome the performance appraisal system in order to achieve its criteria in term of their relevance, reliability, free from bias and practicality.